Medical Students' Perceptions of Patient-Doctor Relationship in South Korea: Concept Mapping Analysis - Yune, So Jung; Kang, Seung Hee; Park, Kwihwa (Frontiers in Public Health, 2021)
Introduction The patient-doctor relationship has evolved from early paternalism to a consumerism and partnership model that emphasizes cooperation. Patient-doctor relationships might vary with the socio-cultural environment, because the medical environment affects such relationships. We investigated the patient-doctor relationship among medical students through concept mapping analysis. Twenty-six fourth-grade Korean medical students wrote a reflection journal and participated in the concept classification and the importance evaluation of the derived concept. ALSCAL multidimensional scaling and Ward hierarchical cluster analysis were performed. Also, the 5-point Likert scale was used to evaluate the importance of the concept. Sixty-six statements about the patient-doctor relationship were extracted and grouped into six clusters. The x-axis is the dimension of “Information-Respect,” and the y-axis is “Changeability-Persistence.” Six patient-doctor concepts were derived and students evaluated “Patient-centered” as the most important. Medical students express various concepts of the patient-doctor relationship. Considering that they may encounter various medical conditions and patients, it is necessary that they understand deeply the complex patient-doctor relationship.